Garahe Leathercraft a production systems study - Abrina, Juan Jr (College of Engineering, 1994)
The study is concerned with the performance of GARAHE's production system. The production organization was analyzed with an objective of improving the current system to make it more effective via the recommended measures. The recommended actions were those that will allow for efficient use of resources and better monitoring and control of production activities. Problems were identified and alternative solutions were generated and evaluated to come up with recommendations. The group first made a thorough analysis of the major aspects of production of GARAHE. The aspects of production tackled were production organization, production flow process, facilities location and layout, tools and equipment, maintenance, forecasting and capacity planning, aggregate planning, materials and inventory management, MRP and CRP, and quality assurance. After analyzing the causes and effects of each problem, the group came up with different solution alternatives. These alternatives were evaluated using the different techniques learned in IE 151. Afterwards the group came up with recommendations of the best alternatives for each aspect of production.